Keabsahan dan Akibat Hukum Perkawinan Penghayat Kepercayaan Pasca Terbitnya Putusan Mahkamah Konstitusi Nomor 97/PUU-XIV/2016 - Safirah Oktavihana; Nindia Putri Prameswari (Notaire, 2021)
Marriage is one of the process of human life as regulated in Article 28B paragraph (1) of the 1945 Constitution of the Republic of Indonesia and also regulated in Article 10 of the Human Rights Law. Marriages conducted by Believers are regulated and protected in the Adminduk Law and the implementing Government Regulations, but not accommodated in Law Number 1 of 1974 on Marriage which is the lex specialist of the regulations governing Marriage in Indonesia. This research uses normative legal research method whose main object is the legal substance of legal protection for Believers on the basis of recognition of belief according to the mandate of the 1945 NRI Constitution, due to incomplete norms and exclusive interpretation of the meaning of the words “God Almighty” and “and trust that”. This research is expected to provide an understanding to stakeholders regarding the validity of marriages conducted by Believers and provide administrative legal protection to Believer. The Constitutional Court Decision Number 97/PUU-XIV/2016 provides legal solutions and protection for Believers for administrative legal arrangements that have not fully protected the existence of believers in the God Almighty. After the issuance of Constitutional Court’s decision, the marriage of Believers was recognized as a legal marriage and brought good legal consequences for their offspring.Keywords: Legal Protection; Believer; Marriage; Law of Administration.Perkawinan adalah salah satu proses kehidupan manusia yang diatur dalam Pasal 28B ayat (1) UUD NRI Tahun 1945 dan diatur pula dalam Pasal 10 UU HAM. Perkawinan yang dilakukan oleh Penghayat Kepercayaan diatur dan dilindungi dalam UU Adminduk dan Peraturan Pemerintah pelaksananya, namun tidak diakomodir dalam UU Nomor 1 Tahun 1974 tentang Perkawinan yang merupakan lex specialis dari peraturan yang mengatur tentang Perkawinan di Indonesia. Penelitian ini menggunakan metode penelitian hukum normatif yang obyek utamanya adalah substansi hukum atas perlindungan hukum bagi Penghayat Kepercayaan atas dasar pengakuan Kepercayaan sesuai amanat UUD NRI Tahun 1945, akibat kekuranglengkapan norma dan penafsiran eksklusif makna kata “Ketuhanan Yang Maha Esa” dan “dan kepercayaannya itu”. Penelitian ini diharapkan dapat memberikan pemahaman kepada para stakeholder terkait Keabsahan Perkawinan yang dilakukan oleh Penghayat Kepercayaan dan memberi perlindungan hukum secara administratif kepada Penghayat Kepercayaan. Putusan Mahkamah Konstitusi Nomor 97/PUU-XIV/2016 hadir memberikan solusi dan perlindungan hukum bagi Penghayat Kepercayaan atas pengaturan hukum administratif yang belum sepenuhnya melindungi dari keberadaan pemeluk Kepercayaan terhadap Tuhan YME. Pasca terbitnya Putusan MK tersebut, perkawinan Penghayat Kepercayaan diakui sebagai perkawinan yang sah dan membawa akibat hukum yang baik bagi anak turunannya. Kata Kunci: Perlindungan Hukum; Penghayat Kepercayaan; Perkawinan; Hukum Administrasi.